2021
DOI: 10.3389/fmicb.2021.698703
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Bacterial Communities of Ginkgo biloba Leaves During Leaf Developmental Period

Abstract: Plant-specialized secondary metabolites have ecological functions in mediating interactions between plants and their entophytes. In this study, high-throughput gene sequencing was used to analyze the composition and abundance of bacteria from Ginkgo leaves at five different sampling times. The results indicated that the bacterial community structure varied during leaf developmental stage. Bacterial diversity was observed to be the highest at T2 stage and the lowest at T1 stage. Proteobacteria, Firmicutes, Acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…This difference might be because these microorganisms in Ginkgo leaves already live in an environment with high flavonoid content and have developed the resistance to flavonoids. Staphylococcus showed a significant negative correlation with T_flavonoid and kaempferol, the same as our previous study ( Deng et al, 2021 ). Thus, we indicated that flavonoids could affect the community’s composition and structure in Ginkgo leaves.…”
Section: Discussionsupporting
confidence: 91%
“…This difference might be because these microorganisms in Ginkgo leaves already live in an environment with high flavonoid content and have developed the resistance to flavonoids. Staphylococcus showed a significant negative correlation with T_flavonoid and kaempferol, the same as our previous study ( Deng et al, 2021 ). Thus, we indicated that flavonoids could affect the community’s composition and structure in Ginkgo leaves.…”
Section: Discussionsupporting
confidence: 91%
“…Highly-diverse endophytic communities can greatly influence the metabolite composition of host plants [ 16 ]. Studies on Ginkgo biloba L. found that endophytic bacteria were significantly correlated with flavonoid concentration and composition.In particular, Staphylococcus was positively correlated with quercetin and variations in the abundance of Staphylococcus showed a strong correlation with flavonoid content [ 17 ]. Gallic acid is the main active component of Cynomorium songaricum and concentration was significantly correlated with most of the dominant endophytic fungi [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The flavonoid biosynthesis in plants mainly originates from the metabolic pathway of phenylalanine ( Kazuki et al, 2013 ; Deng et al, 2021 ). Phenylalanine is catalyzed by phenylalanine ammonia-lyase (PLA) key enzymes to produce cinnamic acid, coumaroyl acid, and caffeoyl acid, and then, they are further catalyzed by 4-coumaric acid CoA ligase (4CL) enzymes to produce a variety of phenylalanine deamination derivatives, including cinnamoyl-CoA, p-coumaroyl-CoA, caffeoyl-CoA, and feruloyl-CoA.…”
Section: Introductionmentioning
confidence: 99%